The Principle of Interdiction in Hidden Compensation or Silent Taxation in Spain - Salvador Fuentes, Ernesto (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2018)
The aim of this article is a deep study of fund transfers within the several tax office rates and to foresee to fit them in the Spanish legal system, particularly in the Constitution and the Organic Law for Local Communities Funding. We will also look into the cases that Spain has produced as well as into the measures taken and also to see whether there is currently any such case. We will go through the special case of concert regime and agreements for the Basque Country and Navarra.